Financial Literacy and Economic Empowerment of PCG Personnel: Basis for a Financial Autonomy Training Course - Shenyl Ivy P. Hernandez (International Journal of Multidisciplinary: Applied Business and Education Research, 2026)
This study assessed the levels of financial literacy and economic empowerment among Philippine Coast Guard (PCG) personnel to inform the development of a tailored Financial Autonomy Training Course. A mixed-methods research design using concurrent triangulation was employed. Quantitative data were collected through a structured survey administered to 400 PCG personnel, including officers, non-officers, and non-uniformed personnel. Qualitative data were gathered through key informant interviews with selected PCG leaders and personnel. Results showed that respondents generally demonstrated high to extremely high levels of financial literacy and economic empowerment. Among the financial literacy dimensions, debt management obtained the highest rating, whereas investing received the lowest rating, indicating limited practical knowledge and participation in investment activities. In terms of economic empowerment, job security and job satisfaction received very high ratings, while work–life balance and purchasing power, although rated high, reflected existing financial and occupational pressures. Qualitative findings indicated that financial literacy initiatives within the PCG were limited, fragmented, and primarily focused on retirement preparation rather than continuous financial capability development. Participants also identified financial stress, limited discretionary income, operational demands, and the absence of a structured financial education program as key challenges. In conclusion, while personnel demonstrated generally positive levels of financial literacy and economic empowerment, gaps remained in investment literacy, long-term financial planning, financial stress management, and institutional support. The findings supported the institutionalization of a tailored Financial Autonomy Training Course to strengthen the financial capability and well-being of PCG personnel.